Health of young athletes: aspects of sports specialization - Huzak, Oleksandra (Journal of Education, Health and Sport, 2016)
Relevance. In modern conditions of development of sports science the process of studying the health of an athlete as a set of physiological, psychological and morphological parameters in dynamically changing conditions of extreme activity is based on the understanding that an appropriate level of health is a necessary and obligatory basis for the reliability of the athlete. The objective of the study is to analyze and systematize the current scientific and methodological knowledge and results of practical experience of domestic and foreign researchers on the health of young athletes. Results. With the proper preparation of the training process, all the adaptation processes that occur in the body of the athlete under the influence of physical activity of different nature, are the basis for achieving sports results, and training and competitive activities create the conditions for the systematic improvement of the reserve capacity of the organism. In cases where the practice of training departs from the classical principles of the theory of periodization, the body of the athlete initially develops a state of increased mobility of adaptation reserves, followed by the breakdown of the compensatory-adaptive mechanisms, which is manifested by the change in the properties of the reactivity and resistance of the organism to the action of harmful agents. Conclusions. Systematization of theoretical prerequisites, which indicate a clear increase in negative tendencies in the state of somatic health of young athletes, with insufficient study of their medical-epidemiological and ontogenetic aspects, in combination with the inability of methodological conditions to realize continuous process of physical function somatic systems and the states that precede them.